High-toughness polyester composition and preparation method thereof

By adopting innovative blending processes in PETG materials, combining additives such as water, antioxidants and other additives with toughening agents for melt blending, the problem of poor compatibility of toughening agents in PETG materials is solved, and high toughness and strength are improved. Broaden the application fields of polyester materials.

CN119144127AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310718858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

During the toughening process, existing PETG materials have problems such as poor compatibility and poor dispersion of tougheners, which leads to increased toughness of the material but higher costs or performance.

Method used

By adopting an innovative blending process, by adding an appropriate amount of water, antioxidants, heat stabilizers, etc. to the PETG material as additive I and the toughening agent for melt blending, forming a high-toughness polyester composition, reducing the amount of toughening agent and Improve its dispersion in the substrate.

Benefits of technology

The high toughness and strength of PETG materials have been improved, and the impact strength has been increased by more than 4 times. At the same time, the tensile and bending strengths have been maintained, the amount of toughening agent is reduced, the problem of poor dispersion of toughening agent is solved, and the polyester material has been broadened. Application field.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-toughness polyester composition and a preparation method thereof, and belongs to the field of polyester. The preparation method of the polyester comprises the following steps: carrying out melt blending on a part of polyester and an additive I to obtain a blend A, carrying out melt blending on the blend A and a flexibilizer to obtain a blend B, carrying out melt blending on the rest of polyester, an additive II and the blend B, and finally extruding and granulating the mixture or preparing the mixture into other proper shapes. The high-toughness polyester composition is prepared by adopting an innovative blending process, so that the dispersity of a toughening agent in a matrix is improved, and the compatibility of the matrix and the toughening agent is improved; meanwhile, it is accidentally found that the polyester composition still keeps excellent toughness and sufficient strength even if the use amount of the flexibilizer is reduced by 50% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester, more specifically to a high-toughness polyester material, and also to a product made from the polyester composition. Background Art

[0002] Polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG) is a type of copolyester material obtained by transesterification and polycondensation of terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM). PETG has excellent transparency, chemical resistance and stress whitening resistance, can be quickly thermoformed or extrusion blow molded, and has been widely used in plates, sheets, cosmetic packaging, etc.

[0003] Household products have higher and higher requirements on materials, and need to toughen PETG. At present, the common toughening method is to add toughening agent. But this method often produces difficult problems such as poor compatibility of components and poor dispersion. Therefore, in order to improve the toughness of PETG material economically and reasonably, a new PETG composition and preparation method thereof need to be provided.

[0004] Chinese patent CN102816414B discloses a highly heat-resistant flame-retardant reinforced PET composition and a preparation method thereof, wherein the notched impact strength of the PET composition is improved by adding a reactive toughening agent. The PET composition comprises: PET, a reactive toughening agent, a nucleating agent masterbatch, a brominated flame retardant, an inorganic flame retardant, a reinforcing agent, a chain extender, a lubricant, and an antioxidant, and the composition is blended by a twin-screw extruder.

[0005] Patent CN105524433A discloses a method for preparing high-toughness PET, which is to add an appropriate amount of branched polystyrene BPS and liquid paraffin to a PET matrix, and prepare a PET / BPS blend by melt blending. The preparation method is simple, but the toughening agent has poor dispersibility; secondly, the addition of liquid paraffin as a compatibilizer will affect the performance of the blend.

[0006] Chinese patent CN112341781A discloses a high elongation sprayed PC / PBT alloy material and its preparation method, which uses a reactive toughening agent and a core-shell structured silicone toughening agent to achieve the purpose of increasing the volume and toughening of the PC / PBT alloy. The PC mass content in the alloy is about 50%, and the manufacturing cost of the alloy is high.

[0007] Chinese patent CN103131138B invented a thermoplastic polyester composition and a preparation method thereof, which improves the toughness of the thermoplastic polyester composition by blending a toughening agent, wherein the toughening agent includes a recycled rubber toughening agent or an impact resin toughening agent. Summary of the invention

[0008] The present invention adopts an innovative blending process to solve the problems of poor compatibility and poor dispersion of the toughening agent in the matrix, and greatly reduces the amount of the toughening agent, thereby achieving reasonable distribution and dispersion of the toughening agent in the matrix, thereby obtaining a high-toughness polyester composition. The product prepared from the composition has excellent toughness and the material also has sufficient strength.

[0009] The purpose of the present invention can be achieved through the following technical solutions:

[0010] A method for preparing a high-toughness polyester composition, the method comprising the following steps:

[0011] (1) melt-blending a portion of the polyester with the additive I to obtain a blend A;

[0012] Additive I is selected from water, diols, dibasic acids, terephthalate polymers, antioxidants, heat stabilizers, branching agents, toners, release agents, flame retardants and any combination thereof;

[0013] (2) melt-blending the blend A and the toughening agent to obtain a blend B;

[0014] (3) The remaining polyester, additive II and blend B are melt-blended, and the mixture is finally extruded and pelletized or made into other suitable shapes.

[0015] The additive II is selected from chain extenders, toners, release agents, antioxidants, flame retardants and any combination thereof.

[0016] In the technical solution of the present invention: the additive I in step (1) is selected from water and an antioxidant, or the additive I is selected from a diol and a terephthalate polymer, or the additive I is selected from a diol, a terephthalate polymer and a heat stabilizer;

[0017] The polyester is selected from polyethylene terephthalate 1,4-cyclohexanedimethanol;

[0018] In some preferred technical schemes: the additive I described in step (1) is selected from water and antioxidant in a mass ratio of 1:20 to 40, or the additive I is selected from terephthalate polymer, diol and heat stabilizer in a mass ratio of 70 to 90:1:5 to 10; or the additive I is selected from diol and heat stabilizer in a mass ratio of 1:5 to 10.

[0019] In the technical solution of the present invention: the intrinsic viscosity of the blend A in step (1) is 0.57-0.67 dL / g, the total amount of terminal carboxyl groups and terminal hydroxyl groups is 120-180 mol / t, and the molar ratio of terminal carboxyl groups to terminal hydroxyl groups is 1:6-1:2.

[0020] In the technical solution of the present invention: at least one toughening agent in step (2) is selected from functionalized maleic anhydride toughening agent, glycidyl methacrylate toughening agent, and styrene block toughening agent.

[0021] In some preferred technical solutions: the toughening agent is KRATON FG1924 or AX8900.

[0022] In the technical solution of the present invention: the weight proportions of polyester, additive I, toughening agent and additive II are 75-95 parts, 0.1-5 parts, 5-20 parts and 0.1-2 parts respectively;

[0023] In the technical solution of the present invention, a portion of the polyester is 5 to 30 wt% of the total amount of the polyester. More preferably, a portion of the polyester is 5 to 20 wt% of the total amount of the polyester.

[0024] In the technical solution of the present invention: the blend A is in a solid state or a molten state, and preferably the blend A is in a molten state.

[0025] In the technical scheme of the present invention: the diol in step (1) is selected from at least one of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, 1,4-cyclohexanedimethanol, isosorbide and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; preferably: the diol is 1,4-cyclohexanedimethanol;

[0026] The dibasic acid in step (1) comprises at least one selected from oxalic acid, malonic acid, succinic acid, adipic acid and 1,4-cyclohexanedicarboxylic acid;

[0027] The terephthalate polymer in step (1) is selected from at least one of PBT, PBA, PBST and PBAT;

[0028] The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 1222;

[0029] The heat stabilizer is selected from at least one of trimethyl phosphate (TMP), triethyl phosphate (TEP), triethyl phosphate (TEPA) and triphenyl phosphate (TPP).

[0030] In the technical solution of the present invention: melt blending uses a melt blender selected from a single-screw or twin-screw extruder, a blender, a kneader, an internal mixer, and an injection molding machine;

[0031] The temperature of the melt blender is between 180 and 260°C, preferably between 200 and 250°C.

[0032] In the technical solution of the present invention: Additive II is antioxidant 1222 or antioxidant 1010.

[0033] A high-tenacity polyester composition is prepared by the above method.

[0034] In the technical solution of the present invention: the high-toughness polyester composition prepared by the above method is used in cosmetic packaging, food utensils, household items, medical equipment, mechanical equipment, indoor and outdoor signs, and furniture and building materials.

[0035] In the technical solution of the present invention: the condition for melt blending is to convey the materials into a twin-screw extruder so that the materials are fully melt blended and uniformly mixed, and the working temperature of the twin-screw extruder is 200°C-260°C.

[0036] In the technical solution of the present invention, the amount of toughening agent used is greatly reduced, and the matrix of the composition can maintain a strong force between molecular chains, ensuring that the polyester composition has sufficient tensile strength.

[0037] In the technical solution of the present invention: a high-toughness polyester composition, the tensile strength of the composition is 40-46MPa, the bending strength is 60-62MPa, and the impact strength is 20-52kJ / m 2 .

[0038] Beneficial effects of the present invention:

[0039] The present invention adopts an innovative blending process to prepare a high-toughness polyester composition, improves the dispersibility of the toughening agent in the matrix, and improves the compatibility between the matrix and the toughening agent; at the same time, it is unexpectedly found that even if the amount of the toughening agent is reduced by more than 50%, the polyester composition still maintains excellent toughness and sufficient strength. Compared with conventional PETG, the impact strength of the polyester composition is increased by more than 4 times without affecting the tensile strength, solving the problem of poor compatibility and poor dispersion of the toughening agent in the matrix, and obtaining a high-toughness and high-strength polyester composition, which has excellent toughness and sufficient strength. It broadens the application field and use area of ​​polyester materials and has great market prospects. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:

[0041] Test method:

[0042] The tensile properties are tested in accordance with GB / T1040.2-2006. The simply supported beam notched impact strength is tested in accordance with GB / T1043-2008.

[0043] Comparative Example 1:

[0044] PETG uses SK Chemical Company's SKYGREEN K2012, 89 parts of PETG, 10 parts of KRATON FG1924 and 1 part of antioxidant 1010 are put into a high-speed mixer, stirred at 500r / min for 5 minutes for premixing, and then the premix is ​​sent to a twin-screw melt extruder for pelletizing, and then an injection molding machine is used to prepare standard test specimens. The melt temperature for extrusion and injection molding is maintained in the range of 200-250℃.

[0045] Comparative Example 2:

[0046] PETG uses SK Chemical Company's SKYGREEN K2012, 79 parts of PETG, 20 parts of KRATON FG1924 and 1 part of antioxidant 1010 are put into a high-speed mixer, stirred at 500r / min for 5 minutes for premixing, and then the premix is ​​sent to a twin-screw melt extruder for pelletizing, and then an injection molding machine is used to prepare standard test specimens. The melt temperature for extrusion and injection molding is maintained in the range of 200-250℃.

[0047] Embodiment 1:

[0048] PETG uses SKYGREEN K2012 from SK Chemical Company.

[0049] Step (1): 5 parts of PETG, 0.005 parts of water and 0.2 parts of antioxidant 1010 are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.58 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0050] Step (2): melt blending the molten state A with 10 parts of KRATON FG1924 in a twin-screw side feeder to obtain a blend B; the melt blending conditions are: the twin-screw side feeder is a twin-screw extruder, KRATON FG1924 is added at the first feed port, and the molten state A is conveyed to the extruder from the melting section feed port. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0051] Step (3): 84 parts of PETG and 0.8 parts of antioxidant 1010 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0052] Embodiment 2:

[0053] PETG uses SKYGREEN K2012 from SK Chemical Company.

[0054] Step (1): 10 parts of PETG, 0.005 parts of water and 0.2 parts of antioxidant 1010 are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.63 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0055] Step (2): melt blending the molten state A with 10 parts of KRATON FG1924 in a twin-screw side feeder to obtain a blend B. The melt blending conditions are as follows: the twin-screw side feeder is a twin-screw extruder, KRATON FG1924 is added at the first feed port, and the molten state A is conveyed to the extruder from the feed port of the melting section. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0056] Step (3): 74 parts of PETG and 0.8 parts of antioxidant 1010 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0057] Embodiment 3:

[0058] PETG uses SKYGREEN K2012 from SK Chemical Company.

[0059] Step (1): 15 parts of PETG, 0.007 parts of water and 0.2 parts of antioxidant 1010 are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.66 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0060] Step (2): melt blending the molten state A with 10 parts of KRATON FG1924 in a twin-screw side feeder to obtain a blend B. The melt blending conditions are as follows: the twin-screw side feeder is a twin-screw extruder, KRATON FG1924 is added at the first feed port, and the molten state A is conveyed to the extruder from the feed port of the melting section. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0061] Step (3): 64 parts of PETG and 0.8 parts of antioxidant 1010 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0062] The test results of the materials of Table 1 Comparative Examples 1-2 and Examples 1-3 are as follows:

[0063] Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Mixture A terminal carboxyl group (mol / t) / / 45 35 38 Terminal hydroxyl group of mixture A (mol / t) / / 134 89 83 Viscosity of mixture A (dL / g) / / 0.58 0.63 0.66 Mixture A raw material (fraction) 0 0 5 10 15 Toughening agent (parts) 10 20 10 10 10 Tensile strength(MPa) 45.9 35.3 45.8 45.2 44.7 Bending strength(MPa) 56.3 45.2 60.5 60.5 61.8 <![CDATA[Impact strength (kJ / m 2 )]]> 12.6 30.8 25.1 45.5 49.8

[0064] The above is a detailed introduction to a high-toughness polyester composition and a preparation method thereof provided by the present invention. It can be seen from Examples 1-3 that as the mass fraction of blend A increases, the toughness of the high-toughness polyester composition increases, and Example 3 has the best toughness. Compared with Example 1 of the conventional process, Example 3 has an impact strength that is nearly 4 times higher, while the tensile strength is equivalent and the bending strength is slightly higher; compared with Example 2 of the high toughening agent dosage, Example 3 has a significant advantage in mechanical strength, and the impact strength is increased by 62%.

[0065] Comparative Example 3:

[0066] PETG uses Eastar GN078 from Eastman Company. 92 parts of PETG, 7 parts of LOTADER AX8900 and 1 part of antioxidant 1222 are put into a high-speed mixer and stirred at 500r / min for 5 minutes for premixing. Then the premix is ​​sent to a twin-screw melt extruder for pelletizing, and then the injection molding machine is used to inject the test specimens. The melt temperature for extrusion and injection molding is maintained in the range of 200-250℃.

[0067] Comparative Example 4:

[0068] PETG uses Eastar GN078 from Eastman Company. 84 parts of PETG, 15 parts of LOTADER AX8900 and 1 part of antioxidant 1222 are put into a high-speed mixer and stirred at 500r / min for 5 minutes for premixing. Then the premix is ​​sent to a twin-screw melt extruder for pelletizing, and then the injection molding machine is used to inject the test specimens. The melt temperature for extrusion and injection molding is maintained in the range of 200-250℃.

[0069] Embodiment 4:

[0070] PETG uses Eastar GN078 from Eastman.

[0071] Step (1): 10 parts of PETG, 0.05 parts of CHDM and 0.35 parts of stabilizer TPP are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.60 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0072] Step (2): melt blending the molten state A with 7 parts of LOTADER AX8900 in a twin-screw side feeder to obtain blend B. The conditions for melt blending are: the twin-screw side feeder is a twin-screw extruder, LOTADER AX8900 is added at the first feed port, and the molten state A is conveyed to the extruder from the melting section feed port. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0073] Step (3): 82 parts of PETG and 0.6 parts of antioxidant 1222 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0074] Embodiment 5:

[0075] PETG uses Eastar GN078 from Eastman Company, and PBT uses XW321 from Yizheng Chemical Fiber Company.

[0076] Step (1): 10 parts of PETG, 4 parts of PBT, 0.05 parts of CHDM and 0.35 parts of stabilizer TPP are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended the mixture using an extruder to obtain a blend A with an intrinsic viscosity of 0.61 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0077] Step (2): melt blending the molten state A with 7 parts of LOTADER AX8900 in a twin-screw side feeder to obtain blend B. The conditions for melt blending are: the twin-screw side feeder is a twin-screw extruder, LOTADER AX8900 is added at the first feed port, and the molten state A is conveyed to the extruder from the melting section feed port. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0078] Step (3): 78 parts of PETG and 0.6 parts of antioxidant 1222 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0079] Embodiment 6:

[0080] PETG uses Eastar GN078 from Eastman Company, and PBS uses TH803S from Blue Mountain Tunhe Company.

[0081] Step (1): 10 parts of PETG, 4 parts of PBST, 0.05 parts of CHDM and 0.35 parts of stabilizer TPP are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.67 dL / g. The high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first, second, third and fourth zones of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0082] Step (2): melt blending the molten state A with 7 parts of LOTADER AX8900 in a twin-screw side feeder to obtain blend B. The conditions for melt blending are: the twin-screw side feeder is a twin-screw extruder, LOTADER AX8900 is added at the first feed port, and the molten state A is conveyed to the extruder from the melting section feed port. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0083] Step (3): 78 parts of PETG and 0.6 parts of antioxidant 1222 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0084] Embodiment 7:

[0085] PETG uses Eastar GN078 from Eastman Company, and PBAT uses TA200 from Yizheng Chemical Fiber Company.

[0086] Step (1): 10 parts of PETG, 4 parts of PBAT, 0.05 parts of CHDM and 0.35 parts of stabilizer TPP are added to a high-speed mixer, stirred at a speed of 500 r / min for 5 minutes, and then melt-blended by an extruder to obtain a blend A with an intrinsic viscosity of 0.66 dL / g. Wherein: the high-speed mixture is added to the feed port of the single-screw extruder, and the temperatures of the first zone, the second zone, the third zone and the fourth zone of the single-screw barrel are set to 220°C, 230°C, 240°C and 240°C, respectively.

[0087] Step (2): melt blending the molten state A with 7 parts of LOTADER AX8900 in a twin-screw side feeder to obtain blend B. The conditions for melt blending are: the twin-screw side feeder is a twin-screw extruder, LOTADER AX8900 is added at the first feed port, and the molten state A is conveyed to the extruder from the melting section feed port. The temperatures of the twin-screw barrel zones 1 to 10 are set to 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 240°C, 240°C, and 245°C, respectively.

[0088] Step (3): 78 parts of PETG and 0.6 parts of antioxidant 1222 were added to the first feeding port of the twin-screw extruder, and the blend B was fed to the second feeding port of the twin-screw extruder by a side feeder, and then the material was extruded and pelletized. A standard test specimen was prepared by an injection molding machine. The melt temperature of the above-mentioned blending extrusion and injection molding process was maintained in the range of 200-250°C.

[0089] Table 2 The test results of the materials of Comparative Examples 3-4 and Examples 4-7 are as follows:

[0090] Comparative Example 3 Comparative Example 4 Example 4 Example 5 Example 6 Example 7 Mixture A terminal carboxyl group (mol / t) / / 42 33 29 30 Terminal hydroxyl group of mixture A (mol / t) / / 106 98 90 94 Intrinsic viscosity of mixture A (dL / g) / / 0.60 0.61 0.67 0.66 Raw materials in the mixture (parts) 0 0 10 10 10 10 Toughening agent (parts) 7 15 7 7 7 7 Tensile strength(MPa) 48.3 40.6 49.3 50.2 51.3 52.3 Bending strength(MPa) 55.3 50.3 60.5 60.5 53.6 52.3 <![CDATA[Impact strength (kJ / m 2 )]]> 13.5 55.8 53.3 56.2 65.3 68.8

[0091] Compared with the conventional process comparative example 3, the impact strength of the high-toughness polyester composition prepared by the unique blending process of the present invention is improved by 3-4 times without affecting the mechanical strength of the material; compared with the high-auxiliary dosage comparative example 4, the mechanical properties of the high-toughness polyester composition prepared by the unique blending process of the present invention have obvious advantages, and the impact performance can also be improved. Therefore, the polyester composition prepared by the present invention has excellent impact resistance, simple production process, low cost, and broad application prospects.

Claims

1. A high-toughness polyester composition, characterized in that: The tensile strength of the composition is 40-46 MPa, the bending strength is 60-62 MPa, and the impact strength is 20-52 kJ / m 2 .

2. A method for preparing the high-toughness polyester composition according to claim 1, characterized in that: The method comprises the following steps: (1) melt-blending a portion of the polyester with the additive I to obtain a blend A; Additive I is selected from water, diols, dibasic acids, terephthalate polymers, antioxidants, heat stabilizers, branching agents, toners, release agents, flame retardants and any combination thereof; (2) melt-blending the blend A and the toughening agent to obtain a blend B; (3) The remaining polyester, additive II and blend B are melt-blended, and the mixture is finally extruded and pelletized or made into other suitable shapes. The additive II is selected from chain extenders, toners, release agents, antioxidants, flame retardants and any combination thereof.

3. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: The additive I in step (1) is selected from water and an antioxidant, or the additive I is selected from a diol and a terephthalate polymer, or the additive I is selected from a diol, a terephthalate polymer and a heat stabilizer; The polyester is selected from polyethylene terephthalate 1,4-cyclohexanedimethanol; Preferably: the additive I in step (1) is selected from water and an antioxidant in a mass ratio of 1:20-40; or the additive I is selected from terephthalate polymer, diol and heat stabilizer in a mass ratio of 70-90:1:5-10; or The additive I is selected from diol and heat stabilizer in a mass ratio of 1:5-10.

4. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: The intrinsic viscosity of the blend A in step (1) is 0.57-0.67 dL / g, the total amount of terminal carboxyl groups and terminal hydroxyl groups is 120-180 mol / t, and the molar ratio of terminal carboxyl groups to terminal hydroxyl groups is 1:6-1:

2.

5. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: In step (2), at least one of the toughening agents is selected from functionalized maleic anhydride toughening agent, glycidyl methacrylate toughening agent, and styrene block toughening agent; Preferably: the toughening agent is KRATON FG1924 or AX8900.

6. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: The weight proportions of polyester, additive I, toughening agent and additive II are 75-95 parts, 0.1-5 parts, 5-20 parts and 0.1-2 parts respectively; Preferably, a portion of the polyester accounts for 5 to 30 wt% of the total amount of polyester; more preferably, a portion of the polyester accounts for 5 to 20 wt% of the total amount of polyester.

7. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: The blend A is in a solid state or a molten state, preferably a molten state.

8. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: The diol in step (1) is selected from at least one of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, 1,4-cyclohexanedimethanol, isosorbide and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; preferably, the diol is 1,4-cyclohexanedimethanol; The dibasic acid in step (1) comprises at least one selected from oxalic acid, malonic acid, succinic acid, adipic acid and 1,4-cyclohexanedicarboxylic acid; The terephthalate polymer in step (1) is selected from at least one of PBT, PBS, PBAT and PBST; The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 1222; The heat stabilizer is selected from at least one of trimethyl phosphate (TMP), triethyl phosphate (TEP), triethyl phosphate (TEPA) and triphenyl phosphate (TPP).

9. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: Melt blending uses a melt blender selected from a single-screw or twin-screw extruder, a blender, a kneader, an internal mixer, and an injection molding machine; The temperature of the melt blender is between 180 and 260°C, preferably between 200 and 250°C.

10. The method for preparing the high-toughness polyester composition according to claim 2, characterized in that: Additive II is antioxidant 1222 or antioxidant 1010.

11. A high-toughness polyester composition, characterized in that: The composition is prepared by the method according to any one of claims 1 to 9.

12. Application of the high-toughness polyester composition obtained by the method of claim 1 in cosmetic packaging, food utensils, household items, medical equipment, mechanical equipment, indoor and outdoor signs, and furniture and building materials.

Citation Information

Patent Citations

  • Preparation method of polyethylene terephthalate / polyterephthalic glycol-1,4-cyclohexanedimethanol ester alloy

    CN101875757A

  • Toughened polyethylene terephthalate glycol (PETG) material and preparation method thereof

    CN102399422A

  • Polyethylene terephthalate glycol (PETG)-acrylonitrile-styrene (AS) blended composite material and preparation method thereof

    CN106751313A

  • High-heat-resistance composition for toys and preparation method thereof

    CN111286167A

  • High-toughness PETG material and application thereof

    CN112266586A

Cited By

  • Forming processing technology of biaxially oriented polymer film

    CN122587261A

  • A forming process for biaxially oriented polymer film

    CN122587261B